REKAYASA PERANGKAT LUNAK SISTEM MONITORING DAN EVALUASI PROGRAM PEMBANGUNAN DESA - Rusdi, Zyad; Trisnawarman, Dedi (Faculty of Information Technology, Universitas Tarumanagara, 2018)
Village development programs are a major concern of the central government. This is manifested in Law no. 6 of 2014 and the substantial distribution of village funds. Villages have considerable authority and resources in realizing the objectives of the village development program. However, the village development process should be monitored and evaluated so that the planned objectives can be realized.This study aims to build an application software that can be used as an instrument to perform monitoring, evaluation and prediction in the process of village development. The method used is a prototyping software engineering method that involves the user and adapted to the dashboard development methodology. Stages of dashboard development consist of identification key perfomance indicator, analysis, function design, dashboard design, and testing.This research produces a web based application software with desapandai.com domain, which can be used to assist village administration in monitoring, evaluation and decision making in village development process.